IMPLEMENTATION OF LITERACY CULTURE IN BUILDING THE THIRDGRADE ELEMENTARY STUDENTS’ CHARACTER - Meylanda Gustina Sari; Zaka Hadikusuma Ramadan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The educational process cannot be separated from reading activities. Through reading, information and knowledge will lead people to goodness. Through reading a lot, everyone will find it easier to solve problems in his/her life. Through reading, everyone will be able to increase the quality of his/her life and even his/her country to be even better. The research objective is to determine literacy culture in building third-grade elementary students’ character. The method used is descriptive qualitative through interview, observation, anddocumentation techniques. The research was conducted at SDN 17 Pekanbaru. The validity testing of the data used triangulation and analysis techniques. The source triangulation used is related to three teachers, three students, and documents. The research results indicate that theliteracy culture at SDN 17 Pekanbaru has been going well. The implementation of literacy culture is carried out by all grade levels from grades 1-6. Literacy activities are carried out in the library and reading corner. There are several activities in the library that have already runwell and are able to foster students' reading and writing interests, making Wall Magazine, group work, fast reading, and reading fairy tales. Literacy in the classroom before starting the learning, students are asked to read books for 15-20 minutes. The characters built in schools through the literacy culture are having faith, fearing God Almighty, having a noble character,having global diversity, working together, being independent, and reasoning critically andcreatively.